The Effect of Language Content-Based Cooperative Learning Against Public Speaking Skills - Rahayu, Enny Rahayu (Indonesian Journal Education, 2022)
This study aims to determine the significance of the effect of cooperative learning on the development of students' speaking skills in public. The population in this study was 100 people and a sample of 10 students as the control class and 10 students as the experimental class. The research instrument is a questionnaire in the form of questions with reference to indicators 1) speaking fluency; 2) accuracy of word choice; 3) sentence structure; 4) intonation of reading sentences and 5) speaking expressions. Data analysis concluded that: (1). The cooperative learning process was carried out well with a 50% presentation in the high category. (2). The tendency of students' speaking ability has a good development tendency with a presentation of 30% in the sufficient category. (3). There is a positive and significant effect of cooperative learning on the development of students' public speaking skills with a connectedness coefficient of 95.6%.